Penerapan Konsep Sistem Pendukung Keputusan terhadap Kepemimpinan dan Komunikasi v 1.0 pada Media Sosial - Sasna Khairunnisa Wibowo; Suharnomo Suharnomo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Social media changes our entire lives, from the mindset, behavior, and way of communicating, these changes sometimes generate friction that produces positive or negative effects, depending on how we say and respond. Leadership begins with how to communicate with others, but the most important thing to know are the types of leadership that are the foundation in building effective and efficient communication. In social media, leaders and communication are among the most important factors that solutions must be solved, problems such as: communication tends to be ineffective and effective because it only focuses on the person's personality and does not focus on the positive things he or she has done; how the solution is given, we almost never find it, that there is and even too many sentences that corner others, dislikes and negative comments that have absolutely no quality to be able to contribute positively to the community and many hoaxes are brought up many of the leadership processes become disrupted. From this problem, we create a leadership intelligence (LI) framework, which is one solution to overcome leadership and communication problems. Implementation of LI is a challenge in our culture, because our culture will affect the quality of communication, and communication is influenced by attitudes, and attitudes influenced by education in the family.